Germline MBD4 Mutations and Predisposition to Uveal Melanoma. (1st April 2020) - Derrien, Anne-Céline; Rodrigues, Manuel; Eeckhoutte, Alexandre; Dayot, Stéphane; Houy, Alexandre; Mobuchon, Lenha; Gardrat, Sophie; Lequin, Delphine; Ballet, Stelly; Pierron, Gaëlle; Alsafadi, Samar; Mariani, Odette; et al.
Abstract: Background: Uveal melanoma (UM) arises from malignant transformation of melanocytes in the uveal tract of the eye. This rare tumor has a poor outcome with frequent chemo-resistant liver metastases. BAP1 is the only known predisposing gene for UM. UMs are generally characterized by low tumor mutation burden, but some UMs display a high level of CpG>TpG mutations associated with MBD4 inactivation. Here, we explored the incidence of germline MBD4 variants in a consecutive series of 1093 primary UM case patients and a series of 192 UM tumors with monosomy 3 (M3). Methods: We performed MBD4 targeted sequencing on pooled germline (n = 1093) and tumor (n = 192) DNA samples of UM patients. MBD4 variants (n = 28) were validated by Sanger sequencing. We performed whole-exome sequencing on available tumor samples harboring MBD4 variants (n = 9). Variants of unknown pathogenicity were further functionally assessed. Results: We identified 8 deleterious MBD4 mutations in the consecutive UM series, a 9.15-fold (95% confidence interval = 4.24-fold to 19.73-fold) increased incidence compared with the general population (Fisher exact test, P  = 2.00 × 10 –5, 2-sided), and 4 additional deleterious MBD4 mutations in the M3 cohort, including 3 germline and 1 somatic mutations. Tumors carrying deleterious MBD4 mutations were all associated with high tumor mutation burden and a CpG>TpG hypermutator phenotype. Conclusions: We demonstrate that MBD4 is a new predisposing gene for UM associated with hypermutated M3 tumors. The tumor spectrum of this predisposing condition will likely expand with the addition of MBD4 to diagnostic panels. Tumors arising in such a context should be recognized because they may respond to immunotherapy.